Temporal replication of the Pullman strain of Aleutian disease virus in royal pastel mink. - Hadlow, W J (1985)
Information was sought on the temporal replication of Aleutian disease virus in 27 royal pastel mink. Groups of three were examined 8 to 126 days after they were inoculated subcutaneously with 10(3) 50% lethal doses of the Pullman strain. Much individual variation was noted in the onset of infection, occurrence of viremia, and extent of virus replication in the tissues. Thus, virus was detected in lymph nodes regional to the site of inoculation in only some mink during the first 14 days after inoculation. During this period, virus was often present as well in the mesenteric lymph node and spleen. First detected on day 10, viremia was present in all mink examined on day 28 but occurred irregularly thereafter, even when virus was widespread in the tissues. Except in five mink succumbing to the disease, the tissue distribution of virus after day 28 tended to be more limited, and the titers were generally lower than they had been earlier. Even though present in the lymph nodes and spleen, virus was often absent from the kidney, liver, and intestine after day 28. Specific antibody was detected on day 28 and was present in all mink thereafter, ostensibly without any adverse effect on virus replication. In most mink, the infection was considered subclinical, for it was usually not accompanied by a rise in serum gamma globulin or by morphologic evidence of the disease. The virologic findings in this study have a bearing on the relationship of subclinical infections to both horizontal and vertical transmission of the virus.